Design and materials development of automotive crash box: a review - Yusof, N.S.B.; Sapuan, S.M.; Sultan, M.T.H.; Jawaid, M.; Maleque, Md. Abdul (Elsevier Espana, 2017)
Recent interest by automotive manufacturing company is to develop a component, capable of enhancing safety features associated with lightweight materials such as using aluminum and composites. The use of aluminum metal matrix composites (MMC) and composite materials improve the performance of an automotive crash box due to their lightweight. Automotive crash box is a component, equipped at the front end of a car, and is one of the most important devices for crash energy absorption. The review is mainly divided by two topics, i.e. design of geometry profiles and the crash box material advancements, both geometry and material properties would influence the efficiency of kinetic energy absorption during collision. This review benefits both academics and corporate sector as it outlines major lines of research in the crash box design. It discusses the results from 3D simulations up to laboratory experiments of crash box specimen and the effect of material selection to the characteristic of crash box device. The information from this paper should stimulate more research and more crash box design solutions to reduce fatal damage during collision in automotive industry.